On The Decay of Br82 - Webster, Ian Bruce (My University, 1964)
Single-crystal, pair, and two-dimensional spectrometry methods have been applied to a study of the decay radiations from 36-hour br82. Two new gamma rays have been discovered and a new energy level in Kr82 has been established. Double and triple gamma summing is discussed. Also regression analysis techniques for coincidence data analysis have been studied. This has been applied to the case of Br82 to derive gamma ray intensities.
Keywords: br82; decay